2017
DOI: 10.1097/gox.0000000000001285
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Needle Structure that Can Avoid Intravascular Injection of Any Filler

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…[2][3][4][5][6] In contrast, it is thought that needles deliver product more precisely and accurately despite creating more trauma to tissue. 7 However, recent studies have shown that using a needle results in less precise product placement, if precision is defined as the filler material remaining in the plane of intended implantation. 4,5 For instance, fluoroscopy X-ray analyses 5 revealed that needle-injected filler material can run retrograde along the created canal which distributes product in all fascial planes, potentially increasing risk for intra-arterial placement.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] In contrast, it is thought that needles deliver product more precisely and accurately despite creating more trauma to tissue. 7 However, recent studies have shown that using a needle results in less precise product placement, if precision is defined as the filler material remaining in the plane of intended implantation. 4,5 For instance, fluoroscopy X-ray analyses 5 revealed that needle-injected filler material can run retrograde along the created canal which distributes product in all fascial planes, potentially increasing risk for intra-arterial placement.…”
Section: Introductionmentioning
confidence: 99%
“…But aspiration is not 100% safe when using smaller gauge needle. 3 Using a blunt cannula is safer but not suitable in every case and cannot provide a very precise injection point if we wanted to place filler just above the bone or in different plane of our face.…”
Section: Discussionmentioning
confidence: 99%
“…We presented a new needle structure that can detect intravascular injection of filler by using the pressure difference between air pressure and intravascular blood pressure. 3 However, there were technical difficulties in making a septum inside the needle lumen in mass production. Therefore, we build a new prototype needle system without the septum that can still prevent intravascular injection by observing blood reflow because of the pressure difference between air and intravascular blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although facial fillers have a low incidence of complications when administered by trained providers, vascular occlusion leading to blindness and stroke continues to be a risk. [3][4][5][6] Injection techniques and methods of filler delivery that help decrease the risk of vascular occlusion are an important growing area of study. This study aimed to demonstrate an experimental model of injecting facial fillers into a simulated bifurcated arterial system using different sized needle gauges at a constant injection pressure.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most feared complications of facial fillers is intravascular occlusion of arteries. 3 The areas with the highest risk of blindness include the nose, forehead, glabellar region, and nasolabial folds due to close collateral circulation that anastamose with the ophthalmic artery. [4][5][6] One anatomic study showed that the range of supratrochlear vessel volumes from the glabella to the orbital apex ranged from 0.04 to 0.12 mL.…”
Section: Introductionmentioning
confidence: 99%